2013
DOI: 10.1542/peds.2012-2191
|View full text |Cite
|
Sign up to set email alerts
|

Functional Abdominal Pain in Childhood and Long-term Vulnerability to Anxiety Disorders

Abstract: WHAT'S KNOWN ON THIS SUBJECT: At the time of their pediatric medical evaluation, patients with functional abdominal pain (FAP) have higher levels of emotional symptoms compared with youth without FAP. No controlled prospective study has evaluated psychiatric outcomes for FAP patients in adulthood. WHAT THIS STUDY ADDS:This prospective study showed that pediatric FAP was associated with high risk of anxiety disorders in adolescence and young adulthood. Risk was highest if abdominal pain persisted, but was signi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

11
168
1
12

Year Published

2014
2014
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 220 publications
(192 citation statements)
references
References 44 publications
(19 reference statements)
11
168
1
12
Order By: Relevance
“…However, comparisons of comorbidity rates across studies should be made with caution because of methodological differences and cohort effects. Although our results suggest that mental disorders precede chronic pain rather than vice versa, there is also some evidence of the reverse direction, 30,88 thereby highlighting the importance of further studying the unfavorable pattern of co-occurring chronic pain and mental disorders.…”
Section: Discussioncontrasting
confidence: 53%
See 1 more Smart Citation
“…However, comparisons of comorbidity rates across studies should be made with caution because of methodological differences and cohort effects. Although our results suggest that mental disorders precede chronic pain rather than vice versa, there is also some evidence of the reverse direction, 30,88 thereby highlighting the importance of further studying the unfavorable pattern of co-occurring chronic pain and mental disorders.…”
Section: Discussioncontrasting
confidence: 53%
“…This is surprising given the developmental trajectory of both conditions. 53,56,60,70,80,83,100 There is particular evidence of the relationship between child/adolescent chronic pain and adult psychiatric symptoms 15, 30,43,60,88 and, vice versa, the relationship between child/ adolescent mental disorders and chronic pain in adulthood. 62,87 Some studies support a relationship between recurrent abdominal pain and mental disorders or symptoms in children and adolescents.…”
mentioning
confidence: 99%
“…For example, recurrent abdominal pain in children has been associated with increased anxiety (Dufton, Dunn, & Compas, 2009;Dufton, Dunn, Slosky, & Compas, 2011;Walker & Greene, 1989). Longitudinal studies from the general population indicate that anxiety can contribute to the development of functional gastrointestinal problems over time (Koloski et al, 2012;Mulvaney, Lambert, Garber, & Walker, 2006), and that anxiety symptoms often pre-date the onset of functional abdominal pain in children (Shelby et al, 2013). Physiological studies have also found evidence of increased physiological stress reactivity (Dufton et al, 2011) and increased auditory startle reflexes (Bakker, Boer, Benninga, Koelman, & Tijssen, 2010) in children with functional abdominal pain.…”
mentioning
confidence: 99%
“…For example, following remission of CRPS, patients may still have chronic pain later even after apparent remission (Anderson and Fallat, 1999). (2) Delayed Relapse – Pain in children may remit and then be present either in a multiple pain format including vulnerabilities of comorbidities (e.g., depression or anxiety) or in the same disease (e.g., irritable bowel syndrome, IBS), years later (Shelby et al, 2013; Walker et al, 2010, 2012). …”
Section: The Tipping Point: Neurobiological Processes Brain Dysfumentioning
confidence: 99%